The Impact of Aged Microglia on D-Serine-Regulated Glutamatergic Transmission - Eugenin-Leon, J (Elsevier, 2021)
Microglia serve a pivotal role in the regulation of the brain environment in neuroinflammation. Their activation depends on highly regulated mechanisms involving various ligands, and pro- and antiinflammatory cytokines. Aging can result in the impairment of microglial functions. Aged microglia become overreactive, contributing to generate an inflammatory and oxidative environment detrimental for neurons and astrocytes. d-serine is an endogenous coagonist of glutamatergic N-methyl-d-aspartate receptor (NMDAR). Through NMDAR coactivation, d-serine participates in synaptogenesis and synaptic plasticity. However, d-serine unbalance can be detrimental for cognitive function and has the potential to induce NMDAR-mediated neuron excitotoxicity. Here, we discuss the mechanisms through which age-dependent changes in microglia affect d-serine balance, and the contribution of d-serine unbalance in the genesis or progression of neurodegenerative pathologies such as Alzheimer disease. © 2021 Elsevier Inc. All rights reserved.